A STUDY OF THE USE OF DIGLOSSIA IN THE MAIN CHARACTER DIALOGUE OF THE PURSUIT OF HAPPINESS MOVIE - CANDRA, RISKI ADE (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Diglossia, Standard English language characterization, Non-standardEnglish language characterization, Language variation factors. In delivering ideas of conversation, language is the most important part to make it success. Language varies according to the social structure of a speech community. This phenomena creates the different use of language for different purpose called Diglossia. There are two varieties in Diglossia, High variety language and low variety language. Standard English language is the example of high variety and non standard English language is the example of low variety language. The researcher conducts a study about diglossia in main character dialogue in “Pursuit of Happiness” movie. There are two problems in this research, namely: (1) What are the English language characteristics of standard language and non-standard language used by main character of “Pursuit of Happiness” movie, and  (2) What are the factors infuencing the main character for using language variety in the “Pursuit of Happiness” movie.This study uses qualitative approach in relation to the use of clear and systematic description about the utterances being studied. Descriptive study in textual analysis is applied in this study to analyze conversation of the main characters through the script and the movie of  “Pursuit of Happiness”.This study reveals that the main character use standard English language by using modal auxiliary, irregular form of the verb to be in the past form and the use ofirregular form of the verb to be in the present form. The main character use Non-standard English language by using Slang words, harsh swearing word, the use of verb ain’t, and combined word that less meaning, The researcher found 5 factors ofmain character to using language variation, those are Gender,  Age, Social classes,Ethnic background, and Speech community.The researcher suggests that for the researchers who are interested in doing research on Diglossia can explore and investigate more about the use of Standard English language and Non-standard English language in real life.